2020
DOI: 10.1002/eap.2074
|View full text |Cite
|
Sign up to set email alerts
|

Plant diversity effect on water quality in wetlands: a meta‐analysis based on experimental systems

Abstract: Citation: Brisson, J., M. Rodriguez, C. A. Martin, and R. Proulx. 2020. Plant diversity effect on water quality in wetlands: a meta-analysis based on experimental systems. Ecological Applications 30(4):Note: -, no residual deviance. FIG. 4. Response ratios and 95% confidence intervals of the removal efficiency of mixtures relative to the best monocultures for total nitrogen (TN) and chemical oxygen demand (COD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 94 publications
(99 reference statements)
0
17
2
Order By: Relevance
“…These results must be nuanced, because multispecies and unvegetated rhizotrons did not show a significant difference in terms of bacterial survival. There is still no clear evidence that, by combining different species with known effects, it would result in a better treatment efficiency for a single contaminant compared to a treatment implying a monoculture [49]. As of now, there is no consistent accordance favoring a monoculture, despite mixed wetlands.…”
Section: Discussionmentioning
confidence: 98%
“…These results must be nuanced, because multispecies and unvegetated rhizotrons did not show a significant difference in terms of bacterial survival. There is still no clear evidence that, by combining different species with known effects, it would result in a better treatment efficiency for a single contaminant compared to a treatment implying a monoculture [49]. As of now, there is no consistent accordance favoring a monoculture, despite mixed wetlands.…”
Section: Discussionmentioning
confidence: 98%
“…Yet, while a greater removal of the polyculture over the average removal of all monocultures taken together may develop, the polyculture may not get necessarily more efficient than the best monoculture. A recent review showed that the advantage of polycultures is more often due to the presence of particularly efficient species in its composition than to a complementarity effect that would lead to a higher efficiency than the best monoculture (Brisson et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Beyond identifying suitable plant species, it has been hypothesised that combining different plant species can improve treatment efficiency (Brisson et al 2020). In some species, differences in root morphology and seasonal activity may lead to more complete spatial and temporal compensation (Coleman et al 2001;Rodriguez and Brisson 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Empirical evidence shows that wetland ecosystem services related to water quality are generally improved by higher plant diversity, including increased nitrogen removal as well as reduced phosphorus loss and methane efflux (Engelhardt and Ritchie, 2001;Bouchard et al, 2007;Brisson et al, 2020). Yet, wetlands are generally highly vulnerable to invasion by exotics (Zedler and Kercher, 2004;Loiselle et al, 2020;Price et al, 2020) and wetland plants are more widely distributed than upland ones (Santamaría, 2002;Ricklefs et al, 2008), which suggests that these ecosystems are prone to biotic homogenization.…”
Section: Introductionmentioning
confidence: 99%
“…Wetlands are receiving increasing attention due to the multiple ecosystem services they provide (MEA, 2005; Maltby and Acreman, 2011), especially in urban areas where they act as critical green infrastructures for flood control, water purification, aesthetics, cooling effect and recreation (Taha, 1997; Bolund and Hunhammar, 1999; Lee and Scholz, 2006; Sun et al, 2012; McLaughlin and Cohen, 2013). Empirical evidence shows that wetland ecosystem services related to water quality are generally improved by higher plant diversity, including increased nitrogen removal as well as reduced phosphorus loss and methane efflux (Engelhardt and Ritchie, 2001; Bouchard et al, 2007; Brisson et al, 2020). Yet, wetlands are generally highly vulnerable to invasion by exotics (Zedler and Kercher, 2004; Loiselle et al, 2020; Price et al, 2020) and wetland plants are more widely distributed than upland ones (Santamaría, 2002; Ricklefs et al, 2008), which suggests that these ecosystems are prone to biotic homogenization.…”
Section: Introductionmentioning
confidence: 99%